2013
DOI: 10.7202/1035577ar
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Pre-service Teachers and Experienced Educators: Social Media for Lifelong Learning

Abstract: Beginning teachers often feel isolated and either lack role models or find it difficult to reach out to more experienced teachers. An educational technology course connected beginning teachers with experienced educators using social media. An analysis of pre-service teachers’ (n=15) reflections indicated that online interactions with experts had provided them with resources, role models, best practice examples, and skills for technology integration and lifelong learning. The results underscore the potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 20 publications
0
10
0
4
Order By: Relevance
“…More recent studies have also included social media tools in the education process (Kumar & Leeman, 2013;Lemon, 2016;Tur & Marin, 2015). These courses have successfully developed various components of TPACK for pre-service teachers.…”
Section: Eurasia J Math Sci and Tech Edmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have also included social media tools in the education process (Kumar & Leeman, 2013;Lemon, 2016;Tur & Marin, 2015). These courses have successfully developed various components of TPACK for pre-service teachers.…”
Section: Eurasia J Math Sci and Tech Edmentioning
confidence: 99%
“…As far as using social media in formal education is concerned, Kumar and Leeman (2013) designed an educational technology course for student teachers of social studies that focused on SMU in the teaching and learning process and in online community building with experts. Their findings indicated that student teachers gained confidence in and knowledge of using new technology and social media in K-12 classrooms.…”
Section: / 12mentioning
confidence: 99%
“…Quant aux téléphones portables, ils offrent lors du stage la possibilité de prendre des photos, de filmer les cours et d'interagir rapidement avec le superviseur ou les collègues (Aubusson, 2009). Aussi, Kumar et Leeman (2013) indiquent que la collaboration peut être facilitée par l'interaction (synchrone ou asynchrone) en ligne sous différentes formes, comme le forum ou le blogue qui favorisent le développement de communautés de pratiques virtuelles porteuses de possibilités d'activités formatrices (Cheon, Lee, Crooks et Song, 2012), de productions par binômes à l'aide d'un forum (Baron et Bruillard, 2006) ou de collaborations entre pairs et avec le superviseur de stage offrant la possibilité d'une rétroaction immédiate (Baran, 2014).…”
Section: Les Possibilités Offertes Par Les Tic Pour Le Développement unclassified
“…La construction du savoir en collaboration peut aussi être favorisée par des outils comme les wikis, le partage de base de données (Aubusson, Schuck et Burden, 2009) qui facilitent l'échange d'expériences pratiques entre enseignants débutants et expérimentés (Kumar et Leeman, 2013) et la résolution de problèmes (Kirschner, Wubbels et Brekelmans, 2008).…”
Section: Les Possibilités Offertes Par Les Tic Pour Le Développement unclassified
See 1 more Smart Citation